DEFINITION wf3_ind()
TYPE =
∀g:G
.∀P:C→C→Prop
.∀n:nat.(P (CSort n) (CSort n))
→(∀c:C
.∀c1:C
.wf3 g c c1
→(P c c1
→∀t:T.∀t1:T.(ty3 g c t t1)→∀b:B.(P (CHead c (Bind b) t) (CHead c1 (Bind b) t)))
→(∀c:C
.∀c1:C
.wf3 g c c1
→(P c c1
→∀t:T
.∀t:T.(ty3 g c t t)→False
→∀b:B.(P (CHead c (Bind b) t) (CHead c1 (Bind Void) (TSort O))))
→(∀c:C.∀c1:C.(wf3 g c c1)→(P c c1)→∀t:T.∀f:F.(P (CHead c (Flat f) t) c1)
→∀c:C.∀c1:C.(wf3 g c c1)→(P c c1))))
BODY =
assume g: G
assume P: C→C→Prop
suppose H: ∀n:nat.(P (CSort n) (CSort n))
suppose H1:
∀c:C
.∀c1:C
.wf3 g c c1
→(P c c1
→∀t:T.∀t1:T.(ty3 g c t t1)→∀b:B.(P (CHead c (Bind b) t) (CHead c1 (Bind b) t)))
suppose H2:
∀c:C
.∀c1:C
.wf3 g c c1
→(P c c1
→∀t:T
.∀t:T.(ty3 g c t t)→False
→∀b:B.(P (CHead c (Bind b) t) (CHead c1 (Bind Void) (TSort O))))
suppose H3: ∀c:C.∀c1:C.(wf3 g c c1)→(P c c1)→∀t:T.∀f:F.(P (CHead c (Flat f) t) c1)
(aux) by well-founded reasoning we prove ∀c:C.∀c1:C.(wf3 g c c1)→(P c c1)
assume c: C
assume c1: C
suppose H4: wf3 g c c1
by cases on H4 we prove P c c1
case wf3_sort n:nat ⇒
the thesis becomes P (CSort n) (CSort n)
by (H .)
P (CSort n) (CSort n)
case wf3_bind c2:C c3:C H5:wf3 g c2 c3 t:T t1:T H6:ty3 g c2 t t1 b:B ⇒
the thesis becomes P (CHead c2 (Bind b) t) (CHead c3 (Bind b) t)
by (aux . . H5)
we proved P c2 c3
by (H1 . . H5 previous . . H6 .)
P (CHead c2 (Bind b) t) (CHead c3 (Bind b) t)
case wf3_void c2:C c3:C H5:wf3 g c2 c3 t:T H6:∀t:T.(ty3 g c2 t t)→False b:B ⇒
the thesis becomes P (CHead c2 (Bind b) t) (CHead c3 (Bind Void) (TSort O))
by (aux . . H5)
we proved P c2 c3
by (H2 . . H5 previous . H6 .)
P (CHead c2 (Bind b) t) (CHead c3 (Bind Void) (TSort O))
case wf3_flat c2:C c3:C H5:wf3 g c2 c3 t:T f:F ⇒
the thesis becomes P (CHead c2 (Flat f) t) c3
by (aux . . H5)
we proved P c2 c3
by (H3 . . H5 previous . .)
P (CHead c2 (Flat f) t) c3
we proved P c c1
∀c:C.∀c1:C.(wf3 g c c1)→(P c c1)
done
consider aux
we proved ∀c:C.∀c1:C.(wf3 g c c1)→(P c c1)
we proved
∀g:G
.∀P:C→C→Prop
.∀n:nat.(P (CSort n) (CSort n))
→(∀c:C
.∀c1:C
.wf3 g c c1
→(P c c1
→∀t:T.∀t1:T.(ty3 g c t t1)→∀b:B.(P (CHead c (Bind b) t) (CHead c1 (Bind b) t)))
→(∀c:C
.∀c1:C
.wf3 g c c1
→(P c c1
→∀t:T
.∀t:T.(ty3 g c t t)→False
→∀b:B.(P (CHead c (Bind b) t) (CHead c1 (Bind Void) (TSort O))))
→(∀c:C.∀c1:C.(wf3 g c c1)→(P c c1)→∀t:T.∀f:F.(P (CHead c (Flat f) t) c1)
→∀c:C.∀c1:C.(wf3 g c c1)→(P c c1))))